Les aires marines protégées en Afrique de l’Ouest : bilan et perspectives vis-à-vis des engagements internationaux - Grégoire Touron-Gardic; Pierre Failler; Oumar Sadio; Idriss Deffry; Marie-Suzanne Traore (Études Caribéennes)
Following long debates, the new global biodiversity framework aims for the legal protection of 30% of the global environment by 2030. This objective follows, among others, Aichi target 11 and Sustainable Development (SDG) 14.5, both of which called for the protection of 10% of the world’s marine surface area. This article presents and explains the differential between the data contained in the world database WDPA, used to measure the progress of countries towards such international commitments, and those that are derived from a comprehensive survey carried out with the administrations of seven West African countries. These countries are far from the goal of 10% marine protected areas, and many priority areas are not covered. In addition to these sites, large offshore marine protected areas are essential to catch up towards international commitments. Nevertheless, the establishment of such MPAs in high seas raises the question of feasibility and equity, in countries where financial, human and technical resources are limited for conservation. Finally, the ‘post-Aichi’ period which freshly began is discussed.